Optimasi Formulasi Esens Sheet Mask Kombinasi Ekstrak Spirulina platensis dan Nanopartikel Bentonit dengan Metode Simplex Lattice Design - Wikantyasning, Erindyah Retno; Nurhakimah, Ulil Fikri; Sula, Ramadhani Dwi; Astuti, Kartika Fidi (Universitas Muhammadiyah Surakarta, 2019)
Spirulina platensis contained phycocyanin that has the potential for antioxidant activity. Bentonite contains various minerals that can absorb water and was known having ability for scavenging of free radicals. The purpose of this study was to obtain the optimum formulae of sheet mask essence, containing combination of Spirulina platensis extract and bentonite nanoparticles and evaluated the antioxidant activity using DPPH (2,2-diphenyl-1-pikrihidrazil) assay. Bentonite nanoparticles was prepared by High Energy Milling (HEM) method and characterized using Particle Size Analyzer (PSA). The results of the nanoparticles characterization was 152,8±0,69 nm for the particle size and 0.106±0.03 for PI value. Physical stability tests showed that the formula was homogenous, viscosity between 0.7-1.1 dPas, and pH between 5-6.5. The IC50 value of Spirulina platensis extract was 256.46 ppm with AAI category was medium. The antioxidant test of this fomula that contain Spirulina platensis extract and bentonite nanoparticles did not show any potential antioxidant activity. The concentrations of PEG 400 and Tween 80 were used to formulate the optimum formula were 4.29% w/w and 6.71% w/w.